Incidence of using partipatory techniques in english teaching process for learning english as a second language in students of IV level at Daniel Octavio Crespo High School, La Concepción, Bugaba, 2013 - Pitty, Kelly; De Gracia, Edward; Vargas, Víctor; Acosta, Jorge (David, Panamá : UDELAS, 2013)
Participatory techniques applied by english teachers should be considered as ways innovate new forms of content orientation. In this way, teh students are active or participate in their own learning process and the acquisition of knowledge achieved.
General Index List of chart List of graph Introduction CHAPTER I: IDENTIFICATION AND PROBLEM STATEMENT CHAPTER II: THEORETICAL 2.1. Teaching techniques 2.1.1. Concept 2.1.2. Types of techniques 2.1.3. Participatory techniques 2.1.4. Use of techniques 2.2. Application of participatory technique 2.2.1. Types of techniques for teaching english process 2.2.2. Procedures for the use of participatory techniques 2.2.3. Resources needed to use the techniques 2.2.4. Interaction of students in the development of the techniques 2.3. Performance scope ot teachers and students in the use of participatory techniques 2.3.1. Class control 2.3.2. Teacher planning and preparation for content 2.3.3. Classroom environment 2.4. Benefits of using participatory techniques 2.4.1. Use of time 2.4.2. Cooperative learning 2.4.3. Motivation and student participation 2.4.4. Communicative development 2.5. Effect of participatory techniques for model of competencies established by the Ministry of Education as a national educational approach 2.5.1. Competence approach 2.5.2. Incidence of participatory techniques for the competence model CHAPTER III: METHODOLOGICAL FRAMEWORK CHAPTE IV: ANALYSIS AND INTERPRETATION OF RESULTS Conclusions Recommendations References
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TECHNIQUES; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA DE INGLÉS; DANIEL OCTAVIO CRESPO HIGH SCHOOL - CHIRIQUÍ